FRI0561 Macrophage pet imaging for predicting treatment outcome of de novo rheumatoid arthritis. (12th June 2018) - Verweij, N.; Bruijnen, S.; Rasch, L.; Turk, S.; Yaqub, M.; Lammertsma, A.; Hoekstra, O.; van Schaardenburg, D.; Voskuyl, A.; Lems, W.; van der Laken, C.
Abstract : Background: Treatment of rheumatoid arthritis (RA) should be initiated as early as possible to prevent further damage and functional disability. 1 However, clinical assessment of treatment response usually takes 12 weeks or longer. Tools that detect earlier response can improve timely treatment decision. Previously, positron emission tomography (PET) using the macrophage tracer [11C]-(R)-PK11195 has shown promise for both early diagnosis and monitoring response to therapy in RA patients. 2, 3 Objectives: To determine the value of [11C]-(R)-PK11195 PET to identify RA responders and non-responders to COBRA-light therapy after 2 weeks of treatment. Methods: Twenty RA patients (female 10/20, age 54±10 years) with clinically active de novo RA based on ACR/EULAR criteria 4 and at least two clinically active joints were included. All patients were given COBRA-light therapy (methotrexate and prednisolone). They received standard clinical care and (clinical) evaluations were performed at 0, 2, 4 and 12 weeks of treatment. Whole body [11C]-(R)-PK11195 PET-CT scans were acquired at baseline and after 2 weeks of treatment. An experienced reader blinded to clinical data scored the 44 joints of the Disease Activity Score (DAS44) visually from 0 to 3. PET response was predefined as either positive if there was a decrease in whole body PET score of ≥10% after two weeks, or as negative if the score increased or remained unchanged. PET outcome was compared with EULAR clinical response at 12 weeks. 5 Results: After 12 weeks of COBRA-light treatment, 16 out of the 20 patients were classified as EULAR responders (13 'good' and 3 'moderate') and 4 patients as non-responders. At baseline, a total of 134 PET positive lesions were observed in the joints of 20 patients, ranging from 1 to 21 lesions per patient. Most frequently, lesions were located in hands and feet: 19% in the wrists (e.g. figure 1A), 37% in the small hand joints and 39% in the small feet joints. After 2 weeks of COBRA light treatment, the number of PET positive lesions decreased to 122 (e.g. figure 1B). A positive whole body PET response was observed in 13 patients. Table 1 shows a side by side comparison between PET response after 2 weeks and EULAR response after 12 weeks. In 15 of the cases (75%), there was an agreement between the PET response and EULAR response. Conclusions: This is the first study to explore the potential of macrophage PET for monitoring therapy in early RA. Preliminary visual assessment demonstrates its ability to monitor arthritis activity changes within 2 weeks of treatment. This offers a window of opportunity for development of precision medicine in the early phase of treatment. Future analyses are in progress to assess whether performance can be further improved by quantification of tracer uptake. References: [1] Smolen JS, et al. Ann Rheum Dis. 2014;73(3):492–509. [2] Gent YY, et al. J Rheumatology2014;41:2145–52. [3] Gent YY, et al. Arthritis Rheum. 2012;64:62–6. [4] Aletaha D, et al. Arthritis Rheum. 2010;62(9):2569–81. [5] Fransen J, et al. Clin Exp Rheumatol. 2005;23(5Suppl 39):S93–9. Disclosure of Interest: None declared